Effect of Astaxanthin Supplementation on Paraoxonase 1 Activities and Oxidative Stress Status in Young Soccer Players. (28th November 2012) - Baralic, Ivana; Djordjevic, Brizita; Dikic, Nenad; Kotur‐Stevuljevic, Jelena; Spasic, Slavica; Jelic‐Ivanovic, Zorana; Radivojevic, Nenad; Andjelkovic, Marija; Pejic, Snezana
<x xml:space="preserve">Abstract</x> The purpose of the study was to examine the effects of astaxanthin (Asx) on paraoxonase (PON1) activities and oxidative stress status in soccer players. Forty soccer players were randomly assigned in a double‐blind fashion to Asx and placebo (P) group. Blood samples were obtained before, 45 and 90 days after supplementation. PON1 activity was assessed by using two substrates: paraoxon and diazoxon. The oxidative stress biomarkers were also examined: total sulphydryl group content (–SH groups), thiobarbituric acid‐reactive substances (TBARS), advanced oxidation protein products and redox balance. The significant interaction effect of supplementation and training (p < 0.05) on PON1 activity toward paraoxon was observed. The PON1 activity toward diazoxon increased in Asx group after 90 days (p < 0.01), while there was no significant difference in P group. SH groups content rose from pre‐ to post‐supplementation period only in Asx group (supplementation and training, p < 0.05; training, p < 0.01). TBARS levels decreased after 45 days and increased after 90 days of regular soccer training in both groups (training, p < 0.001). Redox balance decreased significantly in response to the regular training, regardless of treatment group (training, p < 0.001). Asx supplementation might increase total SH groups content and improve PON1 activity through protection of free thiol groups against oxidative modification. Copyright © 2012 John Wiley & Sons, Ltd.